2021
DOI: 10.1088/1361-6463/ac0b73
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ce doping on the structural, transport and magnetic properties of Sr2IrO4 epitaxial films

Abstract: Sr 2 IrO 4 is predicted to be superconducting and has received extensive attention in the field of high-temperature superconducting. Bulk Sr 2 IrO 4 can be converted to a metallic state by slight chemical doping. Here we studied the structure, morphology, transport and magnetism of (Sr 1−x Ce x ) 2 IrO 4 (x = 0, 0.0125, 0.025, 0.05) epitaxial films grown on (LaAlO 3 ) 0.3 (Sr 2 AlTaO 6 ) 0.35 substrates. Unlike the bulk Sr 2 IrO 4 material, the doped Sr 2 IrO 4 epitaxial film maintains a wide range of Mott var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…What is more interesting is that another λ-like feature appears at low temperature region ( 15 K) of the M ∼ T curves in the 0.06 x 0.2 samples. To our best knowledge, no previous literature have reported this low temperature λ-like feature in undoped or doped Sr 2 IrO 4 systems [21][22][23][24][26][27][28][29]. Thus it is suggested that this feature is originated from the magnetism of Mn ions.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…What is more interesting is that another λ-like feature appears at low temperature region ( 15 K) of the M ∼ T curves in the 0.06 x 0.2 samples. To our best knowledge, no previous literature have reported this low temperature λ-like feature in undoped or doped Sr 2 IrO 4 systems [21][22][23][24][26][27][28][29]. Thus it is suggested that this feature is originated from the magnetism of Mn ions.…”
Section: Resultsmentioning
confidence: 93%
“…For examples, a lot of rare earth elements have been chosen to dope at the Sr site of Sr 2 IrO 4 . In spite of a few reports of insulating-to-metal transition in doped single crystals, in most cases, the Sr 2−x RE x IrO 4 (RE = rare earth elements) polycrystalline samples exhibit insulating behaviors at low temperatures [21][22][23][24]. Besides, a recent work reports a persistent insulating state of Sr 2 IrO 4 upon application of pressure up to megabar [25].…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectra of both samples display the characteristic peaks of the crystalline WO 3 (Figure e) . In addition to the Raman peaks of 357 and 451 cm –1 that represent the basic vibration mode of the crystalline WO 3 , two extra peaks at 275 and 784 cm –1 for IrW/WO 3 -NS-A indicate the stretching vibration of W–O–W binding, reflecting the distortion of WO 3 framework due to the introduced Ir. …”
Section: Resultsmentioning
confidence: 96%
“…Exploring the optical and electronic properties of rare-earth (RE) compounds have been a challenging field of research now a days [1][2][3][4][5][6][7][8][9]. The primary driving force behind those studies rely on the fact that most RE compounds not only show nonlinear optical properties useful for second harmonic generations (SHGs) but also find wide applications as electro-optic components, optical fibers, laser diodes and in solar cells [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%